2020
DOI: 10.1186/s40364-020-00230-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ferroptosis in breast cancer

Abstract: Ferroptosis is a recently discovered distinct type of regulated cell death caused by the accumulation of lipid-based ROS. Metabolism and expression of specific genes affect the occurrence of ferroptosis, making it a promising therapeutic target to manage cancer. Here, we describe the current status of ferroptosis studies in breast cancer and trace the key regulators of ferroptosis back to previous studies. We also compare ferroptosis to common regulated cell death patterns and discuss the sensitivity to ferrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 315 publications
(375 reference statements)
1
72
0
Order By: Relevance
“…Ferroptosis is a novel form of regulated cell death characterized by destruction of intracellular redox balance and non-apoptosis [ 5 ]. Ferroptosis has become a promising therapeutic option for triggering cancer cell death [ 6 ]. It is reported that siramesine and lapatinib are effective ferroptosis inducers in breast cancer [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a novel form of regulated cell death characterized by destruction of intracellular redox balance and non-apoptosis [ 5 ]. Ferroptosis has become a promising therapeutic option for triggering cancer cell death [ 6 ]. It is reported that siramesine and lapatinib are effective ferroptosis inducers in breast cancer [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While successful treatment paradigms have emerged for breast cancers expressing estrogen, progesterone, or Her2 receptors, triple negative breast cancers (TNBCs) that do not express any of these receptors are refractory to conventional chemotherapeutics and have a markedly poor prognosis [ 8 ]. Well-established chemical inducers of ferroptosis, such as the GPX4 inhibitor Rsl-3 and the xCT inhibitor Erastin, and their derivatives, are currently being explored as potential therapeutics for breast cancer therapy and have been shown to exert toxicity in these and other cancer cells [ 9 ]. On the other hand, what determines the sensitivity and resistance of cells to these compounds is a critical issue that must be further explored to develop ferroptotic induction as a valid therapeutic strategy for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a novel form of cell death related to iron-caused accumulation of lipid reactive oxygen species (ROS) ( Dixon et al, 2012 ). Accumulating studies have indicated that targeting ferroptosis may be a feasible strategy for therapy of breast cancer and ovarian cancer ( Li et al, 2020 ). It was proposed that triple negative breast cancer (TNBC) patients were more sensitive to ferroptosis than estrogen receptor ( Wang et al, 2021 )-positive patients, which provided a potential therapeutic strategy for TNBC patients ( Doll et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%